OPTIMISASI KONTROL PID UNTUK MOTOR DC MAGNET PERMANEN MENGGUNAKAN PARTICLE SWARM OPTIMIZATION - Muhammad Ruswandi Djalal; Rahmat Rahmat (LPPM STMIK Pringsewu, 2017)
To maximize the performance of DC motors, the proper use of the controller is crucial. Design of Proportional Integral Derivative (PID) controller on dc motor has been done frequently. The use of PID controllers requires proper parameter setting to achieve optimal performance on the motor. Commonly used is the trial-error method, to determine the parameters of the PID controller, but the results obtained do not make the PID controller optimal and will actually damage the system. Therefore, in this research we will propose one of PID parameter tuning method, that is by using Particle Swarm Optimization (PSO), to optimize and determine the proper parameters of PID. PSO is one of the smart methods inspired by the behavior of particles that search for food sources in groups, this concept is adapted and applied into intelligent algorithms to solve optimization problems. From the results obtained the PSO method can well tune the parameters of PID, where for Kp 57.2409, ki = 23.7090, and kd = 9.3575. Response speed after PID receiver, resulting overshoot does not exist and settling time is very fast.